2024
DOI: 10.3390/app14051760
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Life Cycle Cost Analysis (LCCA) for Optimized Decision Making in Adobe Construction Materials

Jorge Albuja-Sánchez,
Andreina Damián-Chalán

Abstract: Adobe construction is a longstanding practice in South America and is characterized by its affordability, accessibility, and ecological sustainability. However, the decision-making process regarding the choice of construction materials often relies on subjective factors, disregarding economic implications throughout the life cycle of a building. This study aimed to introduce life-cycle cost analysis (LCCA) as a valuable tool for optimizing decision making in the context of adobe construction materials in South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…They also highlighted the importance of including an environmental assessment component to quantify the environmental impacts associated with each life cycle phase. Additionally, another study by Garcia et al [111] suggested the integration of life-cycle thinking into building design and construction processes to optimize material selection, construction techniques, and end-of-life strategies. By incorporating life-cycle analysis methodologies into decision-making processes, stakeholders can make more informed choices to minimize environmental impacts and improve the overall sustainability of adobe structures.…”
Section: Discussionmentioning
confidence: 99%
“…They also highlighted the importance of including an environmental assessment component to quantify the environmental impacts associated with each life cycle phase. Additionally, another study by Garcia et al [111] suggested the integration of life-cycle thinking into building design and construction processes to optimize material selection, construction techniques, and end-of-life strategies. By incorporating life-cycle analysis methodologies into decision-making processes, stakeholders can make more informed choices to minimize environmental impacts and improve the overall sustainability of adobe structures.…”
Section: Discussionmentioning
confidence: 99%